IMPLEMENTASI PENDIDIKAN AKHLAK DALAM UPAYA MEMBINA KEPRIBADIAN PADA SISWA MAN PURWOKERTO 2 KABUPATEN BANYUMAS - Irfangi, M. (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2017)
Efforts to develop the personality of students serves as a guide to be able to select and determine an action and then specify which ones are good and which are bad. Fostering personality dimasud here is coaching includes habits, attitudes, and the nature or essential nature which is reflected in the attitude of someone who distinguish with others. Forms of Implementation of moral education in an effort to foster Muslim personality for students MAN Purwokerto 2 Banyumas Regency there are two, the first is coaching in the field of sharia and the second development in the field of morals. In the field of sharia that perform the obligatory prayers in congregation, praying Duha before starting learning and fasting on Mondays and Thursdays, while in the field of morals prepared Trening proselytizing activities to prepare materials such as doing good fellow, mutual respect and mutual trust, honesty, courtesy, behave good, using Islamic dress. Impact of moral education in an effort to build a Muslim personality in MAN Purwokerto 2 Banyumas Regency, had a great impact on students' attitudes change and influence the behavior of religious and moral and religious knowledge of students.Key Words: Implementation of Moral Education and Character Bulding.